Application and Evaluation of a Care Plan for Enhanced Recovery After Thyroidectomy. - Lei Zheng; Shiyu Zhang (Inquiry (00469580))
Purpose: To develop and evaluate a nursing care plan based on the ERAS (Enhanced Recovery After Surgery) approach for thyroid surgery patients. Methods: A nursing care plan has been developed after the literature review and focus group discussion. The content was validated using the Delphi method. Then, a quasi-experimental study was designed. A total of 120 cases with thyroid surgery at Ruijin Hospital from March to June 2018 were divided equally into an ERAS group and a conventional group Results: The nursing care plan consisted of 13 first-level and 32 second-level indicators. (P < .001). Strikingly the outcomes, such as pain scores, length of hospital stay, and hospitalization costs, were significantly less in the ERAS group than those in the conventional group (P<.001), while no difference was detected in the postoperative complications rate. Conclusion: A scientific and reliable nursing care plan has been used for thyroidectomy patients to enhance recovery.